Exploration of Tumor Immunotherapy Strategy Based on STING Signaling Pathway - Zhang, Fan (International Journal of Public Health and Medical Research, 2026)
With the rapid development of tumor immunotherapy, the quality of life of tumor patients has been greatly improved, but the low response rate and drug resistance of individual treatment methods still plague clinical practice. The interferon gene stimulating factor signaling pathway discovered in recent years serves as an important bridge between innate immunity and adaptive anti-tumor immunity, and is currently a highly promising new target for tumor immunotherapy. This pathway can be activated by abnormal DNA in the cytoplasm, inducing strong expression of type I IFN and pro-inflammatory cytokines, and reshaping the immunosuppressive tumor microenvironment, thereby transforming cold tumors into hot tumors in immunology. This article aims to systematically elucidate the combination therapy approach guided by the STING pathway, summarize the types and development of STING agonists, and provide a detailed summary of the methodological basis, synergistic mechanisms, and latest research progress of the combination use of STING agonists with other immune checkpoint blockers, radiotherapy and chemotherapy drugs, tumor vaccines, targeted therapy drugs, and other congenital immune agonists, cell therapy, etc. Finally, summarize the current status and future research directions of the research field in which this article is located. By rational design and optimization of joint strategies, targeting the STING pathway is expected to overcome the limitations of existing immunotherapy and bring clinical benefits to more cancer patients.